2015
DOI: 10.1016/j.biopsych.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Medial Prefrontal-Hippocampal Connectivity and Motor Memory Consolidation in Depression and Schizophrenia

Abstract: While both patient groups showed similar deficits in consolidation associated with hippocampal-prefrontal cortex connectivity, other activity patterns more specific for disease pathology differed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 58 publications
6
82
2
Order By: Relevance
“…Our findings showed that SCZ patients had mainly altered FC with bilateral cerebellum posterior lobe, anterior and middle cingulate cortex, precuneus, and frontal-temporal system at baseline and follow-up, which align with the most common finding in the literature [25,26], indicating decreased FC between the left hippocampus and bilateral precuneus [27], the abnormal FC degree of hippocampal-prefrontal cortex during a sequential finger-tapping task [25], reduced FC between the hippocampus and distributed brain regions in SCZ patients [24]. Furthermore, numerous diffusion tensor image (DTI) studies have also indicated a disruption of neuronal fibers between the left posterior hippocampus and the PCC [28], and there are these reductions of the anatomical connectivity between the hippocampus and other regions [13].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings showed that SCZ patients had mainly altered FC with bilateral cerebellum posterior lobe, anterior and middle cingulate cortex, precuneus, and frontal-temporal system at baseline and follow-up, which align with the most common finding in the literature [25,26], indicating decreased FC between the left hippocampus and bilateral precuneus [27], the abnormal FC degree of hippocampal-prefrontal cortex during a sequential finger-tapping task [25], reduced FC between the hippocampus and distributed brain regions in SCZ patients [24]. Furthermore, numerous diffusion tensor image (DTI) studies have also indicated a disruption of neuronal fibers between the left posterior hippocampus and the PCC [28], and there are these reductions of the anatomical connectivity between the hippocampus and other regions [13].…”
Section: Discussionsupporting
confidence: 92%
“…In healthy individuals, significant performance improvements occur after sleep but not after wake (49, 93-95) and correlate with N2 duration (49) and spindle density (50, 96, 97). In contrast, chronic medicated SZ patients fail to show significant sleep-dependent improvement despite normal learning during training (31, 73, 98-100) and this failure correlated with sleep spindle density in one study (31), but not in two others (73, 100). SZ patients also show reduced sleep-dependent consolidation on a mirror tracing procedural motor task despite intact initial learning.…”
Section: Reduced Spindles Are Associated With Impaired Cognition and mentioning
confidence: 86%
“…Recent work places deficient sleep-dependent memory consolidation among the cognitive deficits of schizophrenia and implicates reduced sleep spindles, a defining electroencephalographic (EEG) feature of Stage 2 non-rapid eye movement sleep (N2), as a potentially treatable mechanism 4 . Schizophrenia patients have deficient sleep-dependent consolidation of both procedural [5][6][7][8][9][10] and declarative 11 memory that, in some studies, correlates with reduced sleep spindle density (spindles per minute) and number 10,11 . These relations are consistent with a large basic literature showing that spindle activity correlates with measures of intelligence and sleep-dependent memory consolidation 12 .…”
Section: Introductionmentioning
confidence: 99%